The Effects of the Addition of Rubber Leaf (Hevea brasiliensis) Flour in Rations on Dry Matter Consumption, Weight Gain and Feed Conversion Ratio of Native Chickens - Armas Hadiyanto; Sri Wigati; Fahmida Manin (Hasanuddin Journal of Animal Science (HAJAS), 2021)
The purpose of the study was to find out the effect of adding rubber leaf (Hevea brasiliensis) flour containing tannin compounds in standard rations on the production performance of native chickens. The materials used were 64 native chickens (32 males and 32 females) aged 8 weeks, rubber leaf flour and non-AGP commercial ration with 21% protein content. The experiment was designed using Randomized Group Design with 4 treatments and 8 repetitions. Grouping was based on sex, and each repetition unit consists of 2 chickens. The treatment given was the addition of rubber leaf flour by 0% (P0), 3% (P1), 6% (P2) and 9% (P3) in 100% of commercial ration given to native chickens raising in individual battery cages for 6 weeks of trial period. The observed variables were consumption of dry matter (DM), weight gain (WG) and feed conversion ratio (FCR). Data were analyzed by Analysis of variance using General Linear Model procedures. The results of statistical analysis showed that the feeding trials affected non-significantly (P >0.05) on all variables observed. DM consumption, Weight Gain and FCR of P0, P1, P2 and P3 treatment group were respectively:  3279, 3260, 3274 and 3355g/head/week; 106.22, 105.15, 99.95 and114.43 g/head/week; 4.88, 5.02; 5.32 and 4.66. Based on the results, it can be concluded that rubber leaf flour can be used up to a level of 9% as alternative to synthetic antibiotic growth promoter (AGP), and produce the same production performance as native chicken production given non-AGP commercial rations. Keywords: Alternative-AGP, Hevea brasiliensis, Native Chicken, Performance, Rubber leaves